Sierra Leone : : Affairs in the Soro chiefdom - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1933)
Typescript and ms. memoranda from the Colonial Office regarding rebellion against the British-supported chief of Soro, led by Isaac Tucker